Critical switching current of a perpendicular magnetic tunnel junction owing to the interplay of spin-transfer torque and spin-orbit torque. (10th August 2021) - Kang, Doo Hyung; Byun, Ji-Hun; Shin, Mincheol
Abstract: Using the linearized Landau–Lifshitz-Gilbert (LLG) equation in the rotation coordinate, we calculate the critical switching current density of a perpendicular magnetic tunnel junction (MTJ), where magnetization switching is achieved by the interplay of spin-transfer and spin-orbit torques. In terms of the critical current density, we find that as the current density inducing the spin-orbit torque ( j SOT ) increases, the current density inducing the spin-transfer torque ( j STT ) decreases nonlinearly. In the presence of the spin-orbit field-like torque ( β ), the critical switching current density by the spin-transfer torque is proportional to the damping constant ( α ) as the conventional spin-transfer torque switching, while the critical switching current density by the spin-orbit torque increases with α when H eff ≫ H SOT . We also investigated the β dependence of the critical switching current density. For a given j SOT, the critical switching current density for the spin-transfer torque, j STT, c decreases linearly with increasing β and nonlinearly decreases with increasing j SOT for a given β . Further, we discuss the β dependence of the critical switching current density on energy.